Monitoring the performances of a maximum power point tracking photovoltaic (MPPT PV) pumping system driven by a brushless direct current (BLDC) motor - Abdellahi, Ba; Mohamed Mahmoud, Mohamed El Mamy; Dah, Ne Ould; Diakité, Amadou; El Hassen, Aroudam; Ehssein, Chighali (International Journal of Renewable Energy Development, 2019)
Nowadays, water pumping systems powered by solar-cell generators are one of the most important applications. It’s a promising alternative to conventional electricity and diesel based pumping systems, especially for applications like community water supplies and irrigation. This study presents a monitored standalone photovoltaic solar direct pumping system using the Maximum Power Point Tracking (MPPT) algorithm to optimize the solar photovoltaic conversion efficiency. It was done at ISET-Rosso in Mauritania. The experimental setup based on Lorentz PS1200C-SJ8-5 pumping system consists of four photovoltaic (PV) panels, inverter PS1200, BLDC motor, centrifugal pump and a storage tank. The system has been monitored, in order to determine the relationship between: the DC power produced by the PV generator and the solar radiation; the water flow and the DC power and by then the relationship between the water flow and the solar radiation. The effect of ambient temperature and solar radiation on the PV panels was also done under Matlab/Simulink environment and compared to the experimental results. ©2019. CBIORE-IJRED. All rights reserved